1998
DOI: 10.3171/jns.1998.88.2.0232
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular decompression of the eighth cranial nerve in patients with hemifacial spasm and incidental tinnitus: an alternative way to study tinnitus

Abstract: It is the authors' opinion that sensorineural hearing loss and positive findings on magnetic resonance imaging are the most reliable evidence for the presence of tinnitus caused by NVC of the eighth cranial nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 19 publications
2
27
0
2
Order By: Relevance
“…This still controversial diagnosis can be based on the clinical picture (18) and confirmed by auditory brainstem responses and magnetic resonance imaging. Results of microsurgical vascular decompression are related to uni-or bi-lateral aspect, the surgical delay, the preoperative hearing status, MRI imaging and gender (10,36,37). Reasonable correlations were found between the localisation of the neurovascular compression, as assessed by neurovascular decompression operation, and the hearing improvement postoperatively (38).…”
Section: Microvascular Compressionsmentioning
confidence: 80%
See 1 more Smart Citation
“…This still controversial diagnosis can be based on the clinical picture (18) and confirmed by auditory brainstem responses and magnetic resonance imaging. Results of microsurgical vascular decompression are related to uni-or bi-lateral aspect, the surgical delay, the preoperative hearing status, MRI imaging and gender (10,36,37). Reasonable correlations were found between the localisation of the neurovascular compression, as assessed by neurovascular decompression operation, and the hearing improvement postoperatively (38).…”
Section: Microvascular Compressionsmentioning
confidence: 80%
“…Compressions of the cochlear nerve can cause incapacitating low pitch pulsatile or high pitch non-pulsatile tinnitus (36). This still controversial diagnosis can be based on the clinical picture (18) and confirmed by auditory brainstem responses and magnetic resonance imaging.…”
Section: Microvascular Compressionsmentioning
confidence: 99%
“…Vascular compression is associated with other disorders such as trigeminal neuralgia, hemifacial spasm, and glossopharyngeal neuralgia (5,6). These syndromes can be treated successfully with microvascular decompression (MVD), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…There is reason to believe that pulsatile tinnitus can occur on a nonacoustic basis, because there have been several reports that neurovascular decompression of the VIII nerve can abolish pulsatile tinnitus (Lesinski, Chambers, Komray, Keiser, & Khodadad, 1979;Ohashi, Yasumura, Nakagawa, Mizukoshi, & Kuze, 1992;Ryu, Yamamoto, Sugiyama, Uemura, & Nozue, 1998). For example, in patients with hemifacial spasm and ipsilateral pulsatile tinnitus, Ryu et al (1998) reported that the pulsatile tinnitus could be abolished with repositioning of a blood vessel compressing the auditory nerve. We conclude that it is likely that all cases of pulsatile tinnitus are not due to somatosounds, but rather, some may have another mechanism, probably neural, such as compression of the auditory nerve by a blood vessel.…”
Section: Somatosensory Pulsatile Tinnitus Syndrome: Somatic Testing Imentioning
confidence: 99%